Protection of medical data in the provision of consumer services: a comparative analysis of some aspects of medical ethics in Kazakhstan and the European Union - Abdrassulova, A.E.; Kostyanaya, Yu.S. (Bulletin of the Karaganda University “Law Series”, 2025)
The ethics of medical research and the confidentiality inherent in doctor-patient relationships and the proper handling of medical data are critically important issues in contemporary medical law across the globe, including Kazakhstan and the European Union. The provision of medical services is inevitably associated with the processing of a large amount of personal data, which is especially “sensitive” than in other areas of consumer services. At the same time, regulation of this issue only by norms on the provision of consumer services is unacceptable. The issue of privacy makes these services a special area that requires more subtle and “smart” regulation. The core tension in this domain arises from conflicting interests: patients seek absolute confidentiality to safeguard their dignity rights, while the broader public interest often necessitates the disclosure of this information for the collective benefit of humanity. Medical data is inherently sensitive and demands a meticulous approach, along with thoughtfully designed legislative frameworks. The European Union has achieved substantial advancements in this area, having developed a robust legal framework and foundational principles, which are explored in this article. Kazakhstan can draw upon this progress in personal data protection within consumer medical services as a valuable model. Medical ethics and confidentiality are multifaceted concepts that can be examined from various perspectives, ranging from philosophical viewpoints to their significant economic implications within the healthcare market. This article examines medical ethics and confidentiality through the lens of Kazakh and European law, highlighting their primary trajectories and evolving trends. The article concludes that the European perspective on medical privacy is among the most highly developed and sound approaches, offering a reliable framework for other legal systems worldwide.